2015
DOI: 10.1088/1742-5468/2015/05/p05016
|View full text |Cite
|
Sign up to set email alerts
|

On the correspondence between a large class of dynamical systems and stochastic processes described by the generalized Fokker–Planck equation with state-dependent diffusion and drift coefficients

Abstract: In this paper using a projection approach and defining the adjoint-Lie time evolution of differential operators, that generalizes the ordinary time evolution of functions, we obtain a Fokker–Planck equation for the distribution function of a part of interest of a large class of dynamical systems. The main assumptions are the weak interaction between the part of interest and the rest of the system (typically non linear) and the average linear response to external perturbations of the irrelevant part. We do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 61 publications
5
30
0
Order By: Relevance
“…10 In Ref. 2, for the specific case we dealt with there, we have shown that this term gives rise exactly to a first order partial derivative; therefore, Eq. (22) results to be a FPE.…”
Section: Perturbation Approaches and The Lie Evolution Of Differmentioning
confidence: 92%
“…10 In Ref. 2, for the specific case we dealt with there, we have shown that this term gives rise exactly to a first order partial derivative; therefore, Eq. (22) results to be a FPE.…”
Section: Perturbation Approaches and The Lie Evolution Of Differmentioning
confidence: 92%
“…In this letter, taking advantage of some recent results of Bianucci [2015aBianucci [ , 2015b (B15 hereafter), we shed some light on this issue. In fact, here we do not use a stochastic force to perturb the ROM but a generic deterministic system that formally represents some model mimicking the MJO/WWB interaction with the ENSO system.…”
Section: 1002/2015gl066772mentioning
confidence: 95%
“…It is proper to observe that according to Bianucci [2015a], the FPE defined by equations (3) and (4) is obtained without hypotheses on the time scale separation between the system of interest (the ROM) and the rest of the system. In fact, in Text S1 in the supporting information, the expressions of the diffusion coefficients are given in terms of the Fourier transform of the normalized autocorrelation function (t) ≡ ⟨ (t) (0)⟩∕⟨ 2 ⟩, exploiting all the possible range of frequencies for the recharged oscillator.…”
Section: The Coupled Model and The Fpementioning
confidence: 99%
“…Using the terminology of the projection approach [31,38,49] the ROM is viewed as the "system of interest" (or system a), while (ξ, π) represent the booster system (or "rest of the system" or system b), namely a set of general chaotic and fast variables, e.g., the MJO and WWB [50][51][52][53][54], that, perturbing the ROM activate the El Niño/La Niña phenomena and which obey some unspecified equations of motion expressed by the generic functions F (ξ, π) and Q (ξ, π). The value of the parameter determines the intensity of the perturbation to the ROM.…”
Section: Conflicts Of Interestmentioning
confidence: 99%